Access all areas? An area-level analysis of accessibility to general practice and community pharmacy services in England by urbanity and social deprivation. Issue 5 (8th May 2015) - Todd, Adam; Copeland, Alison; Husband, Andy; Kasim, Adetayo; Bambra, Clare
Abstract : Objectives: (1) To determine the percentage of the population in England that has access to a general practitioner (GP) premises within a 20 min walk (the accessibility); (2) explore the relationship between the walking distance to a GP premises and urbanity and social deprivation and (3) compare accessibility of a GP premises to that of a community pharmacy—and how this may vary by urbanity and social deprivation. Design: This area-level analysis spatial study used postcodes for all GP premises and community pharmacies in England. Each postcode was assigned to a population lookup table and Lower Super Output Area (LSOA). The LSOA was then matched to urbanity (urban, town and fringe, or village, hamlet and isolated dwellings) and deprivation decile (using the Index of Multiple Deprivation score 2010). Primary outcome measure: Living within a 20 min walk of a GP premises. Results: Overall, 84.8% of the population is estimated to live within a 20 min walk of a GP premises: 81.2% in the most affluent areas, 98.2% in the most deprived areas, 94.2% in urban and 19.4% in rural areas. This is consistently lower when compared with the population living within a 20 min walk of a community pharmacy. Conclusions: Our study shows that the vast majority of the population live within a 20 min walk of a GP premises, with higher proportions in the most deprived areas— a positive primary care law . However, more people live within a 20 min walk of a community pharmacy compared with a GP premises, and this potentially has implications for the commissioning of future services from these healthcare providers in England.